Accounting for Growth Effects of Age Structure Transition through Public Education Expenditure: New Macroeconomic Evidence from India. (December 2018) - Narayana, M. R.
This article quantifies the growth effects of age structure transition through current public education expenditure. Using the National Transfer Accounts' (NTA) First Demographic Dividend (FDD) model, growth effects are accounted by the impact of current public education expenditure on economic support ratio (ESR) and labour productivity through human capital investments. The results offer new macroeconomic evidence. Age structure transition reduces the education dependency ratio (EDR) by all levels of education but the highest in the elementary education. This impacts on a long-term decline in enrolment in elementary education where the current gross enrolment ratio (GER) is close to 100 per cent and a decline in current public education expenditure. Other things being equal, the resultant potential savings, or the availability of extra budgetary resources, is a new way of financing the investment requirements for secondary and higher education with the aim of increasing national economic growth through human capital investments. In particular, growth effects are shown to be positive, higher and longer up to 2050, if the current public education spending is reallocated more for the secondary and higher education. Surprisingly, growth effects are explained less by the ESR than labour productivity. This justifies a higher human capital investment to enhance labour productivity for attainment of higher economic growth. The afore- mentioned macroeconomic framework, results and implications are of general relevance for other developing countries in South Asia and elsewhere in the world. JEL Classification: E65, H52, J11